PENGARUH PEMBERIAN LATIHAN MENGUNYAH MENGGUNAKAN PERMEN KARET TERHADAP JUMLAH SEKRESI SALIVA PADA PASIEN DENGAN DIABETES MELITUS TIPE 2 - Karuniawati, Putri (Coping: Community of Publishing in Nursing, 2015)
The number of salivary secretion in patients with diabetes mellitus has decreased. This is caused by high blood glucose levels, causing thickening of the basement membrane in the small blood vessels that lead to the problem microangiopathy. Microvascular damage or microangiopathy also occurs in the salivary glands. Chewing is a mechanical activity in the mouth that can stimulate receptors of taste. The stimulus is a stimulation of the parasympathetic nervous then dilate blood vessels in order to drain the salivary gland saliva. This study aims to determine the effect of exercise using chewing gum to total salivary secretion in patients with type 2 diabetes mellitus who performed in hospitals Sanjiwani Gianyar. This research is a quasi experimental design (pretest and posttest with control group design). The sample consisted of 30 patients with type 2 diabetes were selected randomly, and then divided into treatment group and control group. The treatment group was given exercises to chew sugar-free gum (xylitol) for 14 days. The results showed an average increase of 0.1133 mL / min in the treatment group, while 0.05 mL / min in the control group. Based on Independent T-test test, this difference was statistically significant with the Sig. (2-tailed) 0.003 which means the provision of training to use chewing gum affect the amount of salivary secretion in patients with type 2 diabetes mellitus
Keywords: diabetes mellitus; chewing; saliva secretion